Chapter Sandfly-Borne Viruses of Demonstrated/Relevant Medical Importance - Charrel, Remi N. (InTechOpen, 2019)
Sandflies show distribution in a vast geographical area from Europe to Asia, Africa, Australia, and Central and South America where they can transmit a large number of viruses. Between these viruses, the most important are grouped into the Phlebovirus genus (family Phenuiviridae). Among them, several sandfly-borne phleboviruses cause self-limiting febrile disease (sandfly fever) or central and peripheral nervous system infections. Data concerning the geographic distribution of these phleboviruses has drastically increased during the last decade in both the new and the old worlds. The current situation depicts a high viral diversity with taxonomic groups containing human pathogenic and non-pathogenic viruses. This merits to provide insight to address the question of medical and veterinary public health impact of all these viruses, which are poorly studied. To do so, integrated and translational approaches must use ecological, epidemiological, serological and direct clinical evidence. Beside, other viruses transmitted by sandflies and belonging to Rhabdoviridae and Reoviridae families can also be of veterinary and public health importance. The chapter aims to provide a comprehensive view of the sandfly-borne viral pathogens of the public health impact on humans and other vertebrates in the old and new worlds.